Trust in International Organizations: An Empirical Investigation Focusing on the United Nations - Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2006)
The literature on social capital has strongly increased in the last two decades, but, there still is a lack of substantial empirical evidence about the determinants of trust. Most studies have focused on social or generalized trust, while those investigating international trust or trust in international organizations are rare. This empirical study analyses a cross-section of individuals using micro-data of the World Values Survey wave III (1995-1997), covering 38 countries, to investigate trust in international organizations, specifically trust in the United Nations. The results suggest that not only socio-demographic and socio-economic factors have an impact on citizens' trust in the UN, but also political factors. We also observe externalities. Political trust at the state level leads to a higher trust at the international level. On the other hand, if a state is perceived as dysfunctional, the level of trust declines.
Keywords: Z13; D73; O19; 330; International Organizations; United Nations; Trust Social Capital; International Perspective; Political Interest